FLT3‐ITD positive acute myeloid leukemia: A retrospective analysis of the role of allogeneic transplant and allelic ratio in patient management. (31st January 2018) - Taylor, Emma; Morris, Kirk; Ellis, Marc; Marlton, Paula; Baveshi, Ketan; Clarey, Joseph; Irving, Ian; Cochrane, Tara; Kennedy, Glen
Abstract: Aim: FMS‐like tyrosine kinase 3‐internal tandem duplication (FLT3‐ITD) positive AML is associated with increased relapse risk and reduced overall survival (OS) compared to non‐FLT3‐mutated AML. The aim of this study was to evaluate the impact of allelic ratio and allogeneic transplant on outcomes in FLT3‐ITD+ AML. Methods: A retrospective study across five centers in Queensland, Australia, was conducted to examine survival outcomes and impact of FLT3‐ITD allelic ratio and allograft. Results: Seventy‐one patients were included in the study. OS was significantly better for patients who were able to be allografted in first complete remission (CR1; 50.1 months vs 8.5 months; P = 0.0002). We did not find allelic ratio to be predictive of outcome. Conclusion: Transplantation in first complete remission is associated with improved outcomes for patients with FLT3+ AML. When feasible transplantation in CR1 is recommended. We do not currently recommend using allelic ratio to stratify risk unless this has been validated by local results.